Gendered Perceptions of Odd and Even Numbers: An Implicit Association Study From Arabic Culture - Jordan, Timothy R.; Yekani, Hajar Aman Key; Sheen, Mercedes (Frontiers in Psychology, 2021)
Previous studies conducted in the USA indicate that people associate numbers with gender, such that odd numbers are more likely to be characterized as male and even numbers as female. It has been argued that this number gendering is probably acquired through social learning and conditioning, where dominant, fundamental cultural values influence the nature of the gender associations made with numbers. However, the incidence of number gendering in “non-Western” cultures outside the USA remains to be fully established. Against this background, the primary purpose of this study was to determine whether people from a culture and country very different from the USA (specifically, native Arabic citizens living in the Arabic culture of the United Arab Emirates) also associate odd and even numbers with gender. To investigate this issue, we adopted the Implicit Association Test used frequently in previous research, where associations between male and female faces and odd and even numbers were examined using both Arabic male and Arabic female participants native to, and resident in, the UAE. The findings indicated that the association of numbers with gender does indeed occur in Arabic culture. But while Arabic females associated odd numbers with male faces and even numbers with female faces (resembling the pattern of previous research in the USA), Arabic males showed the opposite pattern of gender associations. These findings are consistent with the view that number-gendering is a widespread phenomenon that exists across very different cultures but suggest that the pattern of number gendering may change across cultures and gender. Further implications for understanding the association of numbers with gender in human societies are discussed.